Jihad in the city: militant Islam and contentious politics in Tripoli - Lefèvre, Raphaël (Cambridge University Press, 2021)
Tawhid was a militant Islamist group which implemented Islamic law at gunpoint in the Lebanese city of Tripoli during the 1980s. In retrospect, some have called it "the first ISIS-style Emirate." Drawing on 200 interviews with Islamist fighters and their mortal enemies, as well as on a trove of new archival material, Raphaël Lefèvre provides a comprehensive account of this Islamist group. He shows how they featured religious ideologues determined to turn Lebanon into an Islamic Republic, yet also included Tripolitan rebels of all stripes, neighbourhood strongmen with scores to settle, local subalterns seeking social revenge and profit-driven gangsters, who each tried to steer Tawhid's exercise of violence to their advantage. Providing a detailed understanding of the multifaceted processes through which Tawhid emerged in 1982, implemented its "Emirate" and suddenly collapsed in 1985, this is a story that shows how militant Islamist groups are impacted by their grand ideology as much as by local contexts - with crucial lessons for understanding social movements, rebel groups and terrorist organizations elsewhere.